Development of Transparent Electrodynamic Screens on Ultrathin Flexible Glass Film Substrates for Retrofitting Solar Panels and Mirrors for Self-Cleaning Function. Issue 15 (2016) - Mazumder, M. K.; Stark, J. W.; Heiling, C.; Liu, M.; Bernard, A.; Horenstein, M. N.; Garner, S.; Lin, H. Y.
ABSTRACT: Development of transparent electrodynamic screens (EDS) printed on ultrathin flexible glass film substrates for retrofitting on solar panels and solar mirrors to perform self cleaning function is reviewed. Large-scale solar plants are generally installed in semi-arid and desert areas where dust layers build up on solar collectors causes major energy-yield loss. Maintaining designed plant capacities requires more than 90% reflectivity for CSP mirrors and 90% transmission efficiency for PV modules; solar collectors must therefore be cleaned at a frequency depending on the rate of dust deposition. Scarcity of water in these regions requires a cleaning method that drastically reduces or eliminates water and the associated labor costs for high efficiency operation of large-scale solar plants. An EDS film consists of rows of interdigitated, transparent conducting parallel electrodes embedded within a flexible ultrathin glass film and an optically clear adhesive film used for retrofitting the film on the surface of solar collectors. When phased voltage pulses activate the electrodes, the dust particles are first electrostatically charged, then repelled and removed from the surface of the solar collectors by Coulomb force, restoring transmission efficiency greater than 90%. The electrodes of EDS are either made from silver nanowire or another conductive transparent material printed on a highly transparent, ultrathin (100-μm thick), flexible borosilicate glass film. Applications of different conducting transparent electrodes and methods of printing are reviewed for optimizing self-cleaning function of solar panels and mirrors.